Strategi Manajemen Konflik Sebagai Upaya Meningkatkan Kinerja Teamwork Tenaga Kependidikan - Wartini, Sri (IPB University, 2015)
The purpose of this research is to explain influence of conflict management strategy on teamwork performance. This kind of conflict can happen to everyone and in any places disregarding status, income and position. Someone who can not manage conflicts will have a threat for his personal performance, and unfortunately, company’s performance will also gain the effect. Accordingly, we need a strategy to manage conflicts as an effort to create a good performance for individual employee performance as well as tha team performance. The population af this research is the entire educational employees in UNNES by taking some samples using propotional sampling to around 88 samples. The result of this research proves that hypothesis stating “conflict management strategy” influenced positively and significantly on teamwork performance is accepted. This explains that conflict management strategy can give contribution to the teamwork performance through employee’s ability to accomodate ideas from partners of work, avoid disputes by respecting each other, maintaining communication and conduct colaboration on working methods. It is suggested that this research should improve strategies in managing conflicts such as strategies to compete at work by giving chance to other partner to use theirs skill in making decision and finding solution to solve the job.Keywords: conflict management strategy, teamwork’s performance, educational employee